Penyuluhan Dan Pendidikan Kesehatan Terhadap Masyarakat Tentang Peradangan Yang Terjadi Pada Lapisan Lambung (Gastritis) - Musdalifah, Musdalifah; Abdullah, Rusli; Herman, Herman; Sembiring, Endam Apulina Br; Arnianti, Arnianti (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Gastritis or ulcer disease is a disease that we are very familiar with in everyday life. This disease is often characterized by heartburn, nausea, vomiting, satiety, stomach pain and so on. The purpose of this Community Service Activity is to prevent complications and improve the health of the community optimally regarding inflammation that occurs in the lining of the stomach (Gastritis). The Community Service Activity Method with the Pre Test - Post Test Design design is by conducting interventions in the form of counseling and health education to the community optimally regarding inflammation that occurs in the lining of the stomach (Gastritis). The results of the Community Service activity showed that there was an increase in the average general knowledge score before the counseling was given, which was 52%, while after the counseling was given, the average knowledge score increased to 85%. The conclusion is that community service activities provide very useful knowledge for the community who participate in counseling and health education for the community about inflammation that occurs in the lining of the stomach (Gastritis).